Intangible Capital, Relative Asset Shortages and Bubbles - Giglio, Stefano (IMF Working Papers; Working Paper, 2011)
We analyze an overlapping generations economy with financial frictions and accumulation of both physical and intangible capital. The key difference between them is that intangible capital cannot be used as collateral for borrowing. As intangibles become more important in production, financial frictions tighten and equilibrium interest rates decline, creating the conditions for the emergence of rational bubbles. We also analyze the question of dynamic efficiency, demonstrating that, in the presence of financial frictions, neither the interest rate test nor the test proposed by Abel and others (1989) are appropriate. Finally we show that, in general, rational bubbles are not Pareto improving in our framework.